Learning motivation and self-assessment in health economics: a survey on overconfidence in healthcare providers - Bushuven, Stefan; Bentele, Michael; Trifunovic-Koenig, Milena; Gerber, Bianka; Bentele, Stefanie; Hagen, Fritz; Schöffski, Oliver; Marung, Hartwig; Strametz, Reinhard (BMJ Open, 2024)
Introduction Lifelong learning is the foundation for professionals to maintain competence and proficiency in several aspects of economy and medicine. Until now, there is no evidence of overconfidence (the belief to be better than others or tested) and clinical tribalism (the belief that one’s own group outperforms others) in the specialty of health economics. We investigated the hypothesis of overconfidence effects and their relation to learning motivation and motivational patterns in healthcare providers regarding healthcare economics. Methods We conducted a national convenience online survey of 116 healthcare workers recruited from social and personal networks to detect overconfidence effects and clinical tribalism and to assess learning motivation. Instruments included self-assessments for five learning dimensions (factual knowledge, skills, attitude, problem-solving and behaviour) and a four-item situational motivation scale. The analysis comprised paired t-tests, correlation analyses and two-step cluster analyses. Results We detected overplacement, overestimation and signs of clinical tribalism. Responders in the physician subgroup rated themselves superior to colleagues and that their professional group was superior to other professions. Participants being educators in other competencies showed high overconfidence in health economics. We detected two groups of learners: overconfident but motivated persons and overconfident and unmotivated learners. Learning motivation did not correlate with overconfidence effects. Discussion We could show the presence of overconfidence in health economics, which is consistent with studies in healthcare and the economy. The subjective perception of some medical educators, being role models to students and having a superior ‘attitude’ (eg, morality) concerning the economy may foster prejudice against economists as students might believe them. It also may aggravate moral distress and disrupts interactions between healthcare providers managers and leaders. Considering the study’s limitations, lifelong interprofessional and reflective training and train-the-trainer programmes may be mandatory to address the effects.
CRIS-Team Scopus Importer:2024-05-10
Keywords: behavior; ealth economics; health education; quality in health care; rationing; risk management